Inquérito sorológico e fatores associados à infecção por Toxocara spp. de bovinos abatidos em frigoríficos da região de Presidente Prudente, São Paulo - Giudice, Paula Andreia Fabris (2020)
The Toxocariasis is one of the most prevalent helmintozoonoses in the world. The transmission to the humans can occur through the ingestion of larvae present in raw or undercooked viscera/tissue from paratenic hosts, most commonly in cattle. However, there is a scarcity of studies on serological survey and the risk factors associated with the toxocariasis in cattle. The aim of the study was to evaluate the prevalence of the anti-Toxocara antibodies in cattle and to determine the risk factors associated with toxocariasis in the region of Presidente Prudente, São Paulo. A total of 553 bovine blood samples were collected in two slaughterhouses in the region of Presidente Prudente, to verify the production of anti-Toxocara antibodies, by using the standardized indirect ELISA test for this purpose. At the time of the slaughter, the cattle owners were invited to take part in the study and a questionnaire was applied to obtain some data related to the sex of the cattle and the characteristics of the properties. The overall prevalence of anti-Toxocara antibodies was 38% (212/553), and 95.66% of the properties had at least one seropositive bovine (22/23). Beef cattle farms (OR = 2.47; 95% CI = 1.21-5.23; p = 0.014) and presence of dogs (OR = 2.39; 95% CI = 1.26-4.80; p = 0.010) or cats (OR = 2.18; 95% CI = 1.41-3.41; p <0.001) on the property were associated with a positive ELISA test. The feedlot system was shown to be a protective factor (OR = 0.37; 95% CI = 0.23-0.60; p <0.001). Regarding dogs, the non-use of commercial feed (OR: 2.09; 95% CI: 1.443-3.028; p = 0.0001), the regular supply of raw meat (OR: 4.88; 95% CI: 3.14-7.72; p <0.001), and the hunting habit (OR: 2.10; 95% CI: 95% CI: 1.44-3.08; p <0.001) were associated with the presence of anti-Toxocara antibodies. These results indicate the exposure of cattle to infection by Toxocara spp. and the possibility of transmission of human toxocariasis through the ingestion of undercooked bovine tissues.